The Routledge history of world peace since 1750
1 online resource.
Keywords: "The Routledge History of World Peace since 1750 examines the varied and multifaceted scholarship surrounding the topic of peace and engages in a fruitful dialogue about the global history of peace since 1750. Interdisciplinary in nature, the book includes contributions from authors working in fields as diverse as history, philosophy, literature, art, sociology, and Peace Studies. The book crosses the divide between historical inquiry and Peace Studies scholarship, with traditional aspects of peace promotion sitting alongside expansive analyses of peace through other lenses, including specific regional investigations of the Middle East, Africa, Latin America, and other parts of the world. Divided thematically into six parts that are loosely chronological in structure, the book offers a broad overview of peace issues such as peacebuilding, state building, and/or conflict resolution in individual countries or regions, and indicates the unique challenges of achieving peace from a range of perspectives. Global in scope and supported by regional and temporal case studies, the volume is an essential resource for educators, activists, and policymakers involved in promoting peace and curbing violence as well as students and scholars of Peace Studies, history, and their related fields."